OTENTISITAS AL-QUR’AN PERSPEKTIF JOHN WANSBROUGH - Ulfiana Ulfiana (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2019)
This paper discusses the views of John Wansbrough, about the authenticity of the Qur'an. The issue raised in this paper is Wansbrough's claim that the Qur'an is an imitation of the Bible. In answering the problem of library research, the researcher uses the description-analytic method through categorization or grouping in accordance with the data obtained. The study found that John Wansbrough's conclusion that the Qur'an was an imitation of the Bible was that the sources of the Qur'an were allegedly derived from previous religious sources, namely Judaism and Christianity. One of the evidences revealed by Wansbrough is by referring to the story of the Prophet Muhammad in QS. al-Isrā’: 1. According to him the story of isrā is a story taken from the previous religion, the exodus of Moses. He strengthened his opinion by explaining that the pronunciation of asrā bi ‘abdihi found elsewhere explained the story of Moses and also the next verse in the QS. al-Isrā’: 2 it shows the story of Moses.